A Geometry problem!

Geometry Level 3

Let p > 1 p > 1 .

In the above circle, A B = 2 p \overline{AB} = 2p and A C = p 2 1 \overline{AC} = p^2 - 1 in right A B C \triangle{ABC} and Q S = 1 \overline{QS} = 1 and Q S B D \overline{QS} \perp \overline{BD} and Q S \overline{QS} bisects B D \overline{BD} .

If the value of p p for which A D B A B C = 8 5 \dfrac{\triangle{ADB}}{\triangle{ABC}} = \dfrac{8}{5} can be expressed as p = a + b c p = \dfrac{a + \sqrt{b}}{c} , where a , b a,b and c c are coprime positive integers, find a + b + c a + b + c .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Apr 16, 2021

Q S \overline{QS} is the perpendicular bisector of B D O Q \overline{BD} \implies \overline{OQ} is a radii of the circle with center O O .

Using the Pythagorean theorem C B = p 2 + 1 \implies \overline{CB} = p^2 + 1 and m A = 9 0 m\angle{A} = 90^{\circ} \implies

m ( C D B ^ ) = m ( C A B ^ ) = 18 0 C B m(\widehat{CDB}) = m(\widehat{CAB}) = 180^{\circ} \implies \overline{CB} is a diameter of the above circle \implies

R = C B 2 = p 2 + 1 2 O S = R 1 B S 2 = R 2 ( R 1 ) 2 = 2 R 1 = R = \dfrac{\overline{CB}}{2} = \dfrac{p^2 + 1}{2} \implies \overline{OS} = R - 1 \implies \overline{BS}^2 = R^2 - (R - 1)^2 = 2R - 1 =

p 2 B S = p B D = 2 p = A P p^2 \implies \overline{BS} = p \implies \overline{BD} = 2p = \overline{AP}

A B D \implies \triangle{ABD} is an isosceles triangle B E \implies \overline{BE} is the \perp bisector of A D \overline{AD} \implies

A D = 2 A E \overline{AD} = 2\overline{AE}

A B C sin ( θ ) = p 2 1 p 2 + 1 \triangle{ABC} \implies \sin(\theta) = \dfrac{p^2 - 1}{p^2 + 1} and cos ( θ ) = 2 p p 2 + 1 \cos(\theta) = \dfrac{2p}{p^2 + 1} \implies

E B = 2 p cos ( θ ) = 4 p 2 p 2 + 1 \overline{EB} = 2p\cos(\theta) = \dfrac{4p^2}{p^2 + 1} and A E = 2 p sin ( θ ) = 2 p ( p 2 1 ) p 2 + 1 \overline{AE} = 2p\sin(\theta) = \dfrac{2p(p^2 - 1)}{p^2 + 1} \implies

A D = 4 p ( p 2 1 ) p 2 + 1 \overline{AD} = \dfrac{4p(p^2 - 1)}{p^2 + 1}

A D B = 1 2 ( A D E B ) = 8 p 3 ( p 2 1 ) ( p 2 + 1 ) 2 \implies \triangle{ADB} = \dfrac{1}{2}(\overline{AD} * \overline{EB}) = \dfrac{8p^3(p^2 - 1)}{(p^2 + 1)^2}

and

A B C = p ( p 2 1 ) A D B A B C = 8 p 2 ( p 2 + 1 ) 2 = 8 5 \triangle{ABC} = p(p^2 - 1) \implies \dfrac{\triangle{ADB}}{\triangle{ABC}} = \dfrac{8p^2}{(p^2 + 1)^2} = \dfrac{8}{5}

5 p 2 = p 4 + 2 p 2 + 1 p 4 3 p 2 + 1 = 0 \implies 5p^2 = p^4 + 2p^2 + 1 \implies p^4 - 3p^2 + 1 = 0 \implies

p 2 = 3 ± 5 2 = ( 1 ± 5 2 ) 2 p = ± ( 1 ± 5 2 ) p^2 = \dfrac{3 \pm \sqrt{5}}{2} = (\dfrac{1 \pm \sqrt{5}}{2})^2 \implies p = \pm(\dfrac{1 \pm \sqrt{5}}{2})

and p > 1 p = ϕ = 1 + 5 2 = a + b c a + b + c = 8 p > 1 \implies p = \phi = \dfrac{1 + \sqrt{5}}{2} =\dfrac{a + \sqrt{b}}{c} \implies a + b + c = \boxed{8} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...